Tasas retrospectivas de crecimiento del coral hermatípico Montastrea annularis (Scleractinia: Faviidae) en arrecifes al sur del Golfo de México - Carricart-Ganivet, Juan P (1994)
Coionies of Montastrea annularis were collected from 10 m deptb at Triángulo Oeste; Alacrán, Cayo Arcas, Cayo Arenas, Isla Verde and Anegada de Adentro coral reefs, in tbe soutb of the Gulf of Mexico. Growth rates were determined retrospectively, using tbe conventional radiographic technique (sclerochronology). Contact prints witb good defmition of tbe growth bands were obtained from 53 colonies. The general averages per year showed tbe lowest growth rate for 1972 (0.72 cm/yr) and the highest for 1991 (1.02 cm/yr), witb an average of 0.86 cm/yr for the 53 colonies. Thls·growth rate is similar to those reported for tbe same speeies and depth in otber Atlantic sites.